Social Marketing Intervention to Engage Older Adults in Balance Workshops for Fall Prevention: A Multicenter Quasi-Experimental Protocol Study - Goethals, Luc; Barth, Nathalie; Hupin, David; Chapoton, Boris; Guyot, Jessica; Celarier, Thomas; Roche, Frederic; Gallopel-Morvan, Karine; Bongue, Bienvenu (Frontiers in Public Health, 2021)
Background: Falls affects one of three people after 65 years old, and it can lead to serious consequences. Scientific evidence point out that physical exercise is the most efficient way to prevent falls among older adults. Objective: The main objective of this study is to determine if a social marketing program can increase the attendance rate of people aged 60 and over at group balance workshops. Methods: This quasi-experimental multicenter study is being conducted in three French Regions (Loire, Haute-Loire and Rhône) over a period of 18 months. The Social Marketing Campaign will be done in three ways. Firstly, a Communication Campaign will take place in the two Test Areas but not in the Control Area. Secondly, flyers have been designed to be distributed by local partners. Finally, conferences for older people will be organized in the areas of intervention in order to reach the target audience for the program. The study will include people aged 60 and older who want to participate in the Balance Program. Results: The Crédit Agricole Loire/Haute-Loire Foundation funded the study and the Jean Monnet University of Saint-Etienne reviewed it. The Ethics Committee of the University Teaching Hospital of Saint-Etienne approved and peer-reviewed it on September 6, 2019, under Reference Number IRBN622019/CHUSTE. Conclusion: The results of this first study will demonstrate whether or not social marketing for promoting group balance workshops in the elderly will increase their attendanceship in adapted physical activity sessions, especially those that prevent falls. Clinical Trial Registration:https://clinicaltrials.gov/ct2/show/NCT04136938, identifier NCT04136938.